Granular cell tumour of tongue: A case report - John Spencer M. Daniels (Saudi Dental Journal)
Granular cell tumour, also known as Abrikossoff tumour, is a relatively uncommon benign neoplasm, which is more commonly found in females in the 4th to 6th decades of life even though it can occur in all ages.It occurs in all areas of the body but about 45–65% of all lesions are reported in the head and neck region. Intraoral lesions represent about 70% of the granular cell tumours of the head and neck, and account for 1/3 of all cases affecting the whole body.Most of the intraoral lesions occur on the tongue, usually on the lateral aspect, followed by the buccal mucosa and hard palate. Although majority of granular cell tumours are benign, some are clinically aggressive and a few frankly malignant forms have been reported. Some benign lesions exhibit surface ulcerations and this clinical appearance, combined with the overlying pseudoepitheliomatous hyperplasia, seen histologically, may lead to misdiagnosis of malignancy if adequate biopsy material was not taken.A case of granular cell tumour which occurred on the midline area of the dorsum of the posterior 1/3 of the tongue is reported in a 20-year-old female patient. It is interesting because the patient was younger than the average age of occurrence and the tumour occurred in a similar site to that of a lingual thyroid. Keywords: Granular cell tumour, Pseudoepitheliomatous hyperplasia, Squamous cell carcinoma of tongue, Lingual thyroid, Dorsum of posterior one-third of tongue